1999
DOI: 10.1046/j.1570-7458.1999.00574.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of floral character on the foraging behaviour of the hoverfly, Episyrphus balteatus

Abstract: A bioassay to examine the foraging behaviour of the aphidophagous hoverfly, Episyrphus balteatus was used in which various stimuli purported to influence flower choice were tested using model flowers. In choice experiments, E. balteatus exhibited enhanced behavioural responses to the colour yellow, as previously seen in Eristalis by several workers. Previous suggestions that the generalist forager E. balteatus has no preference for colour are re‐examined in the light of this new evidence. The other advertiseme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 26 publications
3
68
0
Order By: Relevance
“…As it has been reported for other insect pollinators (Lunau & Wacht 1994;Sutherland et al 1999;Briscoe & Chittka 2001), the colour preference by Lepidoptera varies among individuals and among the species studied. For example, green colour is not attractive for feeding but it induces oviposition in females of some butterflies, such as Papilio demoleus (L., 1758) (Vaidya 1969) and P. aegeus Donovan, 1805 (Kelber 1999).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…As it has been reported for other insect pollinators (Lunau & Wacht 1994;Sutherland et al 1999;Briscoe & Chittka 2001), the colour preference by Lepidoptera varies among individuals and among the species studied. For example, green colour is not attractive for feeding but it induces oviposition in females of some butterflies, such as Papilio demoleus (L., 1758) (Vaidya 1969) and P. aegeus Donovan, 1805 (Kelber 1999).…”
Section: Discussionsupporting
confidence: 58%
“…Blue and green colours are stimuli both for feeding and egg-laying in Pieris brassicae (David & Gardiner 1961;Scherer & Kolb 1987;Weiss & Papa 2003). It has been reported that the syrphid hoverfly Episyrphus balteatus (De Geer, 1776) strongly prefers yellow flowers for foraging, moreover, small flowers have more visitors than the large artificial flowers (Sutherland et al 1999). Thus, several experimental studies have clearly proved that preference of yellow is innate in many insect pollinators (Kay 1976;Lunau & Wacht 1994;Odell et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of this species might have resulted in hoverfl ies being equally distributed across the different treatments. Moreover, ladybeetles and hoverfl ies are sensitive to colour, especially yellow (Sutherland et al, 1999;Mondor et al, 2000). Hoverfl ies are also sensitive to fl owers with a contrasting UV-pattern (Koski & Ashman, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At the base of each of the stamens in the interior series there are two glands which produce small amounts of concentrated nectar (Rodríguez et al 2001). Small, shiny glands containing low volumes of highly concentrated nectar, either solid on the surface of the nectary or sequestered in tissue (Gilbert 1981), are common in syrphidpollinated flowers (Fleming et al 2007, Sutherland et al 2003, Arroyo & Dafni 1995, Muraoka & Watanabe 1994, Ivri & Dafni 1977. Syrphid flies have also been found to have an innate foraging response to visual pollen signals, specifically points of light precisely in the spectral reflectance range of yellow pollen.…”
Section: Number Of Individuals Proportion Of Pollen % (N)mentioning
confidence: 99%